Factors affecting psychological well-being of college students in the solo raya region: The influence of helicopter parenting and fear of negative evaluation - Pinasti, Esa Sapna; Hertinjung, Wisnu Sri (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
Students have many tasks that indirectly require support from their surroundings to survive and have good psychological well-being. Students with good psychological conditions can learn how to adapt and fully carry out lectures. Often, students have problems such as stress, depression, and anxiety disorders that affect their psychological well-being. This study aimed to examine the relationship between helicopter parenting and fear of negative evaluation on students' psychological well-being. This study used a quantitative correlational method with 366 students in Solo Raya. This study used the Helicopter Parenting scale, the Fear of Negative Evaluation scale, and the psychological well-being scale. The data analysis used is multiple regression analysis, showing a significant relationship between Helicopter Parenting and Fear of Negative Evaluation with the Psychological Well-Being of Greater Solo students (F = 201.490, p <0.01). It was also found that there is a negative relationship between Helicopter Parenting and Psychological Well-Being of Greater Solo students (r = -.495; p < 0.01) and a negative relationship between Fear of Negative Evaluation and Psychological Well-Being of Greater Solo students. Students' level of psychological well-being in this study is classified as moderate, so it is necessary to reduce Helicopter Parenting and Fear of Negative Evaluation by improving communication patterns with parents and fostering self-confidence in individuals to manage negative criticism from the surrounding environment.